2022
DOI: 10.3389/fphar.2022.850176
|View full text |Cite
|
Sign up to set email alerts
|

Target-Based Virtual Screening of Natural Compounds Identifies a Potent Antimalarial With Selective Falcipain-2 Inhibitory Activity

Abstract: We employed a comprehensive approach of target-based virtual high-throughput screening to find potential hits from the ZINC database of natural compounds against cysteine proteases falcipain-2 and falcipain-3 (FP2 and FP3). Molecular docking studies showed the initial hits showing high binding affinity and specificity toward FP2 were selected. Furthermore, the enzyme inhibition and surface plasmon resonance assays were performed which resulted in a compound ZINC12900664 (ST72) with potent inhibitory effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…As can be seen in Figure S32 (Supporting Information) there is either none or very minimal decrease (in case of 4K90, 6VSI and 7CR5) in intramolecular hydrogen bonding in complexes over the period of 50 ns. The PDF analysis also suggests constancy and does not show any significant change in intramolecular hydrogen bonding [114] …”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…As can be seen in Figure S32 (Supporting Information) there is either none or very minimal decrease (in case of 4K90, 6VSI and 7CR5) in intramolecular hydrogen bonding in complexes over the period of 50 ns. The PDF analysis also suggests constancy and does not show any significant change in intramolecular hydrogen bonding [114] …”
Section: Resultsmentioning
confidence: 81%
“…The PDF analysis also suggests constancy and does not show any significant change in intramolecular hydrogen bonding. [114] Overall, the MD simulations that were conducted revealed that the RMSD and RMSF values of the protein-ligand complexes indicated structural deviations and flexibility during the simulation. Despite an initial increase in RMSD upon binding with Terrestrol A(10), the complex remained stable throughout the entire simulation, rendering it an ideal system for further analysis.…”
Section: Dynamics Of Hydrogen Bondingmentioning
confidence: 96%
“…A study by Rosmalena et al has shown that cinchona alkaloid derivatives have shown inhibitory action against FP-2 [ 41 ]. Uddin et al have also shown the inhibitory action of falcipain-2 against natural compounds [ 42 ]. In the present study, we have used 340 plant-derived alkaloids against FP-2 to identify the potential antimalarial agents.…”
Section: Discussionmentioning
confidence: 99%
“…51 Previous works by different research groups have identified hits against FP2. 13,46,49,50 A molecular docking study was conducted and a similar binding pose of 3-(1-benzoyl-5-(4fluorophenyl)-4,5-dihydro-1H-pyrazol-3yl)-7-(diethylamino)-2Hchromen-2-one and epoxysuccinate in FP2 inhibition was observed. 13 Also, an in vitro validation study on the antiplasmodial activity of an acyl-hydrazone-based molecular hybrid against cysteine protease FP2 in silico was conducted.…”
Section: Introductionmentioning
confidence: 96%